A cross-sectional study in adiponectin, glucose metabolism, and body composition in cystic fibrosis - Nielsen, Bibi Uhre; Mikkelsen, Christine Råberg; Oturai, Peter Sandor; Krogh-Madsen, Rikke; Katzenstein, Terese Lea; Ritz, Christian; Pressler, Tacjana; Almdal, Thomas Peter; Mathiesen, Inger Hee Mabuza; Faurholt-Jepsen, Daniel (Frontiers in Endocrinology, 2024)
Objective: We hypothesized that the insulin-sensitizing adipokine adiponectin (ADP) is upregulated in cystic fibrosis (CF) related diabetes (CFRD) and underweight adults with CF. We aimed to assess correlations between glucose metabolism, body composition and ADP in CF. Methods: We performed a cross-sectional study among adults with CF at the Copenhagen CF Center. The study included a fasting level of ADP, an oral glucose tolerance test (OGTT), and a dual energy-x-ray absorptiometry scan. Results: In total, 115 patients were included of whom 104 had an OGTT performed. Glucose intolerance was not correlated with ADP in multivariable analysis, while increased hepatic insulin resistance (i.e., HOMA-IR) was correlated with reduced ADP levels. ADP declined by 4% (eβ 0.96, 95% CI: 0.94, 0.98), 5% (eβ 0.95, 95% CI: 0.93, 0.98), 9% (eβ 0.91, 95% CI: 0.87, 0.95), and 83% (eβ 0.17, 95% CI: 0.08, 0.37) for each one unit (kg/m2) increase in body mass index, fat mass index, muscle mass index, and bone mineral content index, respectively. Conclusions: In CF, ADP was negatively correlated with hepatic insulin resistance as well as low fat, muscle, and bone mass, but not with glucose intolerance. This suggests that malnutrition leads to higher ADP levels in CF.